DEVELOPMENT OF PROFESSIONAL ACTIVITIES OF PHYSICAL EDUCATION TEACHERS IN COMPREHENSIVE SCHOOLS (Web of Teachers: Inderscience Research, 2024)
The ways of using the most effective methods of improving the qualifications of physical education teachers of comprehensive schools are determined. The dissertation describes in detail the methods of working with students, the use of modern technologies, the effective organization of the processes of practical training of teachers and educators beginning their teaching activities.